The Effect of the Game-Based Learning Model on Student Engagement in History Learning - Rahmawati, Vini; Umamah, Nurul; Sumardi, Sumardi; Marjono, Marjono (History Department, Semarang State University and Historian Society of Indonesia, 2023)
This study aimed to examine the effect of the game-based learning model on student engagement in history learning. A quasi-experimental design with a post-test-only model and a non-equivalent control-group design was used to verify the effect of the two variables. The sample consisted of 66 students in classes XI IPS 4 and XI IPS 1 at SMA Negeri 1 Gambiran, obtained through a homogeneity test. The data were collected using documentation and questionnaires. The data analysis technique used one-way ANOVA and LSD (Least Significant Difference) follow-up test with the help of SPSS 22.0 software for Windows. Data analysis results showed that there was an effect of applying the game-based learning model on student engagement in history classrooms. The results of the one-way ANOVA test showed that the probability value (sig.) in the experimental group was 0.040 0.05, with the LSD follow-up test LSD of 2.45455. Therefore, it is concluded that there was an effect of student engagement on the experimental group taught using the game-based learning model. This research recommends that the game-based learning model can be a reference for improving student engagement, active learning, and student-centered learning so that the learning process becomes fun, interactive, communicative, collaborative, and able to maximize the role of technology in education.Keywords: Education 4.0, game-based learning, student engagementPenelitian ini bertujuan untuk menguji pengaruh penerapan model game-based learning terhadap student engagement pada mata pelajaran sejarah. Desain quasi experimental dengan model post-test-only , non-equivalent control-group design digunakan untuk memverifikasi pengaruh kedua variabel. Sampel terdiri dari 66 peserta didik pada kelas XI IPS 4 dan XI IPS 1 di SMA Negeri 1 Gambiran, yang diperoleh melalui uji homogenitas. Pengumpulan data menggunakan dokumentasi dan angket. Teknik analisis data menggunakan one-way anova dan uji lanjut LSD (Least Significant Difference) berbantuan software SPPS 22 for Windows. Hasil analisis data menunjukkan bahwa terdapat pengaruh penerapan model game-based learning terhadap student engagement pada mata pelajaran sejarah. Hasil uji one-way anova menunjukkan probabilitas value (sig.) pada kelompok eksperimen sebesar 0.040 0.05, dengan uji lanjut LSD sebesar 2,45455. Sehingga disimpulan bahwa terdapat pengaruh student engagement pada kelompok eksperimen yang dibelajarkan menggunakan model game-based learning. Rekomendasi penelitian ini adalah model game-based learning mampu menjadi acuan untuk meningkatkan student engagement, karena pembelajaran aktif, student-centered learning sehingga proses pembelajaran menjadi menyenangkan, interaktif, komunikatif, kolaboratif, dan mampu memaksimalkan peran teknologi dalam pembelajaran.Keywords: Pendidikan 4.0, game-based learning, student engagement